Development and validation of the NCC‐BC‐A scale to assess patient‐reported outcomes for breast cancer patients in China - Fei Ma; Xiaoyan Yan; Xiuwen Guan; Tianmou Liu; PRO‐BC China Standards Committee (Cancer Innovation)
Abstract Background The commonly used international patient‐reported outcome scales for breast cancer were developed before the advent of multiple targeted therapies and immunotherapies, rendering them potentially insufficient for current clinical practices. Therefore, it is necessary to develop a specific patient‐reported outcome scale tailored for breast cancer patients in China to optimize the management model for these patients. Methods A comprehensive literature search was performed in the PubMed, Embase, Wanfang, and CNKI databases to extract dimensions and items for a potential patient‐reported outcome scale. The Delphi method was used to modify, add, subtract, and adjust the language of items until the experts reached a consensus on the first draft. This draft was further refined using a cognitive test and a presurvey. The optimized scale was used for a formal survey, and the items were further analyzed and screened using metrics such as the coefficient of variation, correlation coefficient, internal item consistency, factor analysis, reliability, and validity. Results A total of 10,954 articles were analyzed, and 237 were used to create a pool of 277 patient‐reported outcome items. Through two rounds of Delphi expert consultation, the experts' authority coefficients were 0.739 and 0.826. After a cognitive test, several items were adjusted to enhance understanding. Further adjustments were made following a presurvey of 200 advanced breast cancer patients, resulting in a 38‐item patient‐reported outcomes scale, termed NCC‐BC‐A. In the national formal survey, 588 advanced breast cancer patients participated. Principal component analysis showed good consistency among the items and sufficient difference between the dimensions. The results were normally distributed with good variation. The Cronbach's α coefficient of the scale was 0.925 and the test–retest reliability was 0.9041. Conclusion The NCC‐BC‐A scale has high validity and reliability. It comprehensively considered the characteristics of systemic treatment for breast cancer, and the specific context within China. Its implementation may help clinicians to pay more attention to quality of life of breast cancer patients and to optimize the system for managing this condition.